2014
DOI: 10.3906/sag-1303-89
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine abnormalities of patients with cleft lip and/or cleft palate during the neonatal period

Abstract: IntroductionCultivated strawberry, Fragaria × ananassa, is the natural hybrid of F. chiloensis and F. virginiana and is thought to be only about 300 years old (Hancock, 1999). Earlier researchers have reported that the cultivated strawberry has very narrow genetic diversity when compared with its progenitor species (Dale and Sjulin, 1990;Hancock, 2006;Horvath et al., 2011). Since the progenitor species can easily be crossed with the cultivated strawberry, several attempts have been made to utilize the wild spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 56 publications
(55 reference statements)
2
17
0
4
Order By: Relevance
“…This relationship implies the existence of mechanical coordination in the growth of the pituitary gland alongside its enclosing skeletal compartment and may cause variations in the size of the gland, which are reflected in the shape and size of the sella turcica. Although some studies have demonstrated a relationship between cleft lip and palate [19][20][21] , Van der Plas et al [22] claimed that the pituitary is not involved in differences in isolated cleft lip and palate. In our study, there were differences between the cleft group and the control group in terms of the shape and size of the sella turcica, but it was only the length of the sella turcica that was higher in the cleft group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship implies the existence of mechanical coordination in the growth of the pituitary gland alongside its enclosing skeletal compartment and may cause variations in the size of the gland, which are reflected in the shape and size of the sella turcica. Although some studies have demonstrated a relationship between cleft lip and palate [19][20][21] , Van der Plas et al [22] claimed that the pituitary is not involved in differences in isolated cleft lip and palate. In our study, there were differences between the cleft group and the control group in terms of the shape and size of the sella turcica, but it was only the length of the sella turcica that was higher in the cleft group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Akin et al reported a prevalence rate of 12.9% for GHD in newborns with cleft lip and palate, considering the fact that syndromic patients with cleft were not included in the statistics. 2 Akin et al 2 screened all the newborns, irrespective of the absence of symptoms, for hypophyseal hormones and showed that 70% of cleft lip and palate patients had hormonal disorder; however, in the present study, only children over 1 year of age were evaluated, who were symptomatic despite therapeutic interventions. Given a high prevalence rate of nutritional disorders in these children during the first year of life, which give rise to growth deficiencies, if a decision is made to carry out growth hormone screening, it is advisable to carry it out at older ages.…”
mentioning
confidence: 69%
“…The incidence of cleft lip and palate has been reported to be 1 in 700 live births, which might be isolated or associated with other syndromes. 1,2 It seems incidence of cleft lip and palate is a little lower in our country as some authors estimated it from 0.8 to 1.03 in 1000 live birth. 3,4 Approximately 250000 children with clefts are born all over the world annually, necessitating complicated and multiple surgeries and special care.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…A series of transcription factors are involved in pituitary gland formation. Neonatal hypopituitarism may occur due to developmental defects of the pituitary gland, genetic mutations, and perinatal and neonatal events (1)(2)(3)(4)(5)(6)(7)(8) (Table 1). Genetic mutations causing hypopituitarism and their sub-groups are shown in Tables 2 and 3 (1,(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%